An examination of the relationship between mental toughness, psychological skills, coaches' ratings, and athletic performance. - Mack, M. G. (Journal of Sport Behavior, 2018)
The primary purpose o f this research was to examine the relationship between mental toughness (MT) and concepts often associated with MT. MT was assessed using the Mental, Emotional, and Bodily Toughness Inventory (MeBTough; Mack & Ragan, 2008). In Study 1, 39 college students completed the measure twice over a two-week interval to examine test-retest reliability. The intraclass correlation coefficient was .92 indicating that MT was reliable. Study 2 consisted of 120 college students who completed the MeBTough and Test of Performance Strategies (TOPS; Thomas, Murphy, & Hardy, 1999). Results found significant relationships between MeBTough scores and all TOPS subscale scores. Participants who reported greater usage ofpsychological skills had higher levels of MT. Study 3 correlated MT with coaches 'ratings of 24 members of an ice hockey team. Results were statistically nonsignificant. Study 4 examined the relationship between MT and performance in 16 members of an intercollegiate volleyball team. Results showed that players who were categorized as higher performing had higher MT scores. Findings affirmed critical relationships between MT and the use of psychological skills and performance but not coaches 'ratings. Discussion focused on the importance of MT, recommendations that mental skills be developed as a way to increase MT, and the practical utility of sport practitioners using MT instruments for assessing MT.